Comparison of Indonesian Population Information System Service Performace Based On Information System Functional Scorecard Theory - Farah, Najla Alia; Herlambang, Admaja Dwi; Rachmadi, Aditya (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
The Balikpapan Population and Civil Registration Office has implemented service automation by using an information system to support the population and civil registration administration services in Balikpapan, Indonesia. The information system implemented is called The Population Administration Information System (SIAK). The office has previously implemented an information system similar to SIAK, namely the Population Administration Organizing System (SPAK). One of the office aims is to improve the quality of SIAK. SIAK quality is improved in order to achieve optimal service. As a step of achieving vision and mission, implementing work functions and optimizing the utilization of information systems, the comparison of information system performance between information systems that have been used with information systems that have previously been used. The guidelines used in assessing the performance of both systems are Information System Functional Scorecard (ISFS) theory. The data collected by questionnaires then conducted Paired-T Test so that the results of the two systems were obtained differences and can be compared to know which system is superior. SIAK is an information system that is declared superior to SPAK. Furthermore, the comparison results become a reference in providing recommendations for SIAK performance improvement based on the performance comparison results with SPAK.